Level of awareness of UTM staff on occupational safety and health at the work place - Idrus, Durrishah; Ab. Rahman, Hamidah; Ashari, Hapriza; Zaini, Fadilah; Jamil, Rossilah; Muktar, Syaharizatul Noorizwan (Faculty of Management and Human Resource Development, 2004)
The purpose of this study is to determine the level of awareness among UTM staff towards safety and health at the workplace. The respondents comprised of 319 academic and non-academic staff who work in faculties that use high risk equipment or substances, namely the Faculty of Education, Faculty of Science, Faculty of Mechanical Engineering, Faculty of Civil Engineering, Faculty of Electrical Engineering, and the Faculty of Chemical Engineering and Natural Resources. Questionnaires were used as the main instrument for obtaining data for this study. The data were analyzed descriptively based on frequency, percentage and mean in order to determine the level of awareness of the respondents towards safety and health. To examine the relationship between demographic factors and respondents awareness towards safety and health, the Pearson Correlation was used. The results showed that UTM staff had a high level of awareness of safety and health based on their overall mean score of 3.97. Aspects of the staffs level of awareness towards safety and health that were studied were policy, procedure, equipment, training, Department of Safety and Health and commitment as well as environment. Further evaluation showed that the dominant factors that influenced the level of awareness of UTM staff with regards to safety and health were training and policy. Findings also showed that demographic factors did not influence the level of awareness, whether directly or indirectly. The factors that were analyzed recorded a level of relationship of <0.20 and 0.20 0.40 only. This indicates a weak correlation. Finally, this study concludes that in order to raise the level of awareness towards safety and health, the Universitys administration should increase the number of training programmes, safety and health awareness campaigns, offer continuous or periodic safety and health programmes and enforce the use of safety equipment by staff involved in high risk tasks.